2023
DOI: 10.1111/nmo.14534
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal‐Specific symptom anxiety in patients with gastroparesis: Relationships to symptom severity and quality of life

Abstract: Background: Gastrointestinal (GI)-specific anxiety has been identified as a treatment target in irritable bowel syndrome. However, GI-specific anxiety has been understudied in other GI functional/motility disorders. Among adults with gastroparesis, we aimed to: (1) initially validate a measure of GI-specific anxiety, the Visceral Sensitivity Index (VSI); and (2) evaluate the relationship between GI-specific anxiety and gastroparesis symptom severity and quality of life, compared to measures of anxiety, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(104 reference statements)
1
1
0
Order By: Relevance
“…When we consider psychological factors that may influence functioning with a chronic digestive disease, we typically separate generalized anxiety or depression from symptom specific anxiety or depression, where the primary source or focus of distress is around the symptoms themselves. Consistent with the literature in esophageal conditions, symptom specific anxiety was associated with greater severity of gastroparesis symptoms and was more strongly correlated than depression, anxiety, or somatization ( 27 ). Similarly, one study found illness perception to be the mediating factor in the relationship between symptom severity and psychological distress ( 31 ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…When we consider psychological factors that may influence functioning with a chronic digestive disease, we typically separate generalized anxiety or depression from symptom specific anxiety or depression, where the primary source or focus of distress is around the symptoms themselves. Consistent with the literature in esophageal conditions, symptom specific anxiety was associated with greater severity of gastroparesis symptoms and was more strongly correlated than depression, anxiety, or somatization ( 27 ). Similarly, one study found illness perception to be the mediating factor in the relationship between symptom severity and psychological distress ( 31 ).…”
Section: Resultssupporting
confidence: 77%
“…Quality of life in gastroparesis seems to be affected by a combination of symptom severity, depression, symptom anxiety, and coping styles ( 5 , 10 , 13 , 20 , 27 , 31 ). The most common health related social need expressed by gastroparesis patients was mental health, followed closely by financial strain and food security ( 20 ).…”
Section: Resultsmentioning
confidence: 99%